Lumen-apposing metal stents for the treatment of pancreatic and peripancreatic fluid collections and bleeding risk: a propensity matched study - Mangiavillano, Benedetto; Lakhtakia, Sundeep; Samanta, Jayanta; Auriemma, Francesco; Vargas-Madrigal, Jorge; Arcidiacono, Paolo Giorgio; Barbera, Carmelo; Ashhab, Hazem; Song, Tae Jun; Pham, Khanh Do-Kong; Teoh, Anthony Y.B.; Moon, Jong Ho; Crinò, Stefano Francesco; Kongkam, Pradermchai; Aragona, Giovanni; De Lusong, Mark A.; Dhar, Jahnvi; Ofosu, Andrew; Ventra, Agostino; Paduano, Danilo; Franchellucci, Gianluca; Repici, Alessandro; Larghi, Alberto; Facciorusso, Antonio; PFC LAMS study group; Memon, Sana Fathima; Vanella, Giuseppe; Valerii, Giorgio; Alhor, Tareq; Huh, Gunn; Akerkar, Shreeram; Yan, Ryan Wai; Nam, Chloe Hiu; Shin, Il Sang; Sakulthongthawin, Pallop; Calabrese, Federica; Rizzatti, Gianenrico; Hassan, Cesare (Endoscopy, 2024)
Introduction Endoscopic ultrasound (EUS)-guided drainage of symptomatic pancreatic fluid collections (PFCs) using the Hot-Axios device has recently been associated with a significant risk of bleeding. This adverse event (AE) seems to occur less frequently with the use of a different device, the Spaxus stent. The aim of the current study was to compare the rates of bleeding between the two stents.Methods Patients admitted for treatment of PFCs by EUS plus lumen-apposing metal stent in 18 endoscopy referral centers between 10 July 2019 and 28 February 2022 were identified and their outcomes compared using a propensity-matching analysis.Results 363 patients were evaluated. After a 1-to-1 propensity score match, 264 patients were selected (132 per group). The technical and clinical success rates were comparable between the two groups. Significantly more bleeding requiring transfusion and/or intervention occurred in the Hot-Axios group than in the Spaxus group (6.8% vs. 1.5%; P = 0.03); stent type was a significant predictor of bleeding in both univariate and multivariate regression analyses (P = 0.03 and 0.04, respectively). Bleeding necessitating arterial embolization did not however differ significantly between the two groups (3.0% vs. 0%; P = 0.12). In addition, the Hot-Axios was associated with a significantly higher rate of overall AEs compared with the Spaxus stent (9.8% vs. 3.0%; P = 0.04).Conclusion Our study showed that, in patients with PFCs, bleeding requiring transfusion and/or intervention occurred significantly more frequently with use of the Hot-Axios stent than with the Spaxus stent, although this was not the case for bleeding requiring embolization.